Ferrite nanoparticle-loaded biochar adsorption material and preparation method thereof

Through the method of treating nitric acid on biochams and oscillation in iron salt and sodium salt solutions, the loaded iron oxygen nanoparticles biological carbon adsorption materials are prepared, which solves the complexity of materials in the existing technology, high cost and small particle size in the existing technology. The secondary pollution problem has achieved efficient and economic heavy metal pollution removal effects.

CN119346065APending Publication Date: 2025-01-24POWERCHINA ZHONGNAN ENG

Patent Information

Application Number
CN202411351673.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

When removing heavy metal pollution in soil in the prior art, the material production process is complex, the cost is high, and the particle size is too small to be separated, causing secondary pollution.

Method used

The biochar is sieved, treated with nitric acid, washed, dried, and then shaken in a mixed solution of iron salt and sodium salt to form a biochar adsorption material loaded with ferrite nanoparticles.

Benefits of technology

This material has excellent arsenic pollution adsorption effect, low usage, high efficiency, simple preparation process, suitable for large-scale production, and has self-supporting properties and suitable particle size to facilitate solid-liquid separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119346065A_ABST
    Figure CN119346065A_ABST
Patent Text Reader

Abstract

The invention discloses a ferrite nanoparticle-loaded biochar adsorption material and a preparation method thereof, and the ferrite nanoparticle-loaded biochar adsorption material is prepared by the following steps: S1, sieving biochar, cleaning and drying to obtain pretreated biochar; s2, adding the pretreated biochar into a nitric acid solution, mixing, cleaning, filtering and drying to obtain a material A; s3, respectively dissolving a water-soluble ferric salt and a water-soluble sodium salt in water to obtain a ferric salt solution and a sodium salt solution, and mixing the ferric salt solution and the sodium salt solution to obtain a solution a; and S4, adding the material A into the solution a, mixing, cleaning, and drying to obtain the ferrite nanoparticle-loaded biochar adsorption material. By controlling the proportion of the components and the proper raw material ratio, the ferrite nanoparticle-loaded biochar adsorption material for the permeable reactive barrier, which is relatively strong in adsorption catalysis capability, can be prepared, and arsenic ions in pollutants can be efficiently adsorbed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of adsorption materials, and in particular to a ferrite nanoparticle-loaded biochar adsorption material and a preparation method thereof. Background Art

[0002] With the rapid development of human activities, industry and agriculture, the problem of heavy metal pollution in land is becoming increasingly serious. Heavy metal pollution in farmland soil has become an environmental issue that people attach great importance to, and the safety of food crops has also come with it. Since heavy metal soil pollution is hidden, lagging, cumulative, and difficult to reversible, it poses a huge challenge to the prevention and control of heavy metal pollution in soil.

[0003] A new type of electric technology remediation combined with permeable reaction wall technology has gradually attracted attention. It introduces permeable reaction wall technology in the electric field to achieve faster removal of pollutants. Compared with traditional soil heavy metal remediation technology, it has the characteristics of less engineering and test cycle, moderate investment cost, and the ability to repair contaminated soil in situ, which can protect the original use to the greatest extent. It is an economically and technically feasible remediation technology. The core of permeable reaction wall technology is the reaction medium, that is, the repair filler, which should be reactive, stable, low-cost and environmentally safe. The commonly used wall reaction medium materials are mainly reducing materials and adsorption materials. Compared with reducing materials, most of the heavy metals remain in the environment after reduction and passivation. Adsorption materials can eliminate potential risks to a greater extent and completely remove them from the environment. In addition, adsorption materials are widely available and inexpensive. Commonly used materials include biochar, expanded soil, diatomaceous earth, etc.

[0004] Biochar is a porous carbonaceous solid formed by carbonization of plant or animal biomass under oxygen-limited conditions. It has a large specific surface area, high cation exchange capacity, and abundant oxygen-containing functional groups, which is very effective in the removal of heavy metal pollutants (Cd 2+ , Pb 2+ However, due to the small adsorption capacity of the original biochar, it needs to be frequently regenerated, which affects its practical application and needs to be modified.

[0005] China's invention patent application publication number CN11113952926B discloses a heavy metal adsorbent for removing arsenic ions from water, and its preparation method and application. The biomass is first subjected to mycelium inoculation culture and pre-treatment such as drying and crushing to induce the formation of a loose porous pore structure inside the biomass, in preparation for subsequent activation. Then, through high-temperature pyrolysis and reaction with solutions such as Fe(NO3)3, a ferrihydrite nanoparticle loading layer is formed on the surface of the biochar, which has an adsorption and precipitation effect on heavy metal arsenic ions. However, the production process of this material is complicated, the production cost is high, and the particle size is too small to be easily separated, causing secondary pollution. Chinese invention patent application publication number CN110964536A discloses an iron-based soil remediation agent and a preparation method thereof, wherein biogas residue is used as the main raw material, supplemented with straw powder, pig manure, and oxalic acid, and odorless biogas residue is obtained under the fermentation of bacteria such as gold; on the other hand, iron salt, calcium salt and biochar are used to prepare iron-calcium loaded biochar, and then the odorless biogas residue, iron-calcium modified biochar, polyacrylic acid and manganese dioxide are mixed to obtain an iron-calcium biogas residue soil remediation agent. The entire preparation process is complicated, and the material needs to be heated at 250-350℃ with hot air and an air volume of 2000-3000m 3 / h air volume, the energy consumption is high. On the other hand, in the soil remediation experiment, the addition amount of the soil remediation agent is 1.0%. If it is applied in actual farmland in the future, there will be problems such as large material demand. Summary of the invention

[0006] In order to overcome the deficiencies of the prior art, the present invention provides a biochar adsorption material loaded with ferrite nanoparticles and a preparation method thereof. The prepared biochar adsorption material loaded with ferrite nanoparticles has excellent adsorption effect on arsenic pollution.

[0007] A method for preparing a biochar adsorption material loaded with ferrite nanoparticles comprises the following steps:

[0008] S1, screening, washing and drying the biochar to obtain pretreated biochar;

[0009] S2, adding the pretreated biochar to the nitric acid solution, mixing, washing, filtering, and drying to obtain material A;

[0010] S3, dissolving a water-soluble iron salt and a water-soluble sodium salt in water respectively to obtain an iron salt solution and a sodium salt solution, and mixing the iron salt solution and the sodium salt solution to obtain a solution a;

[0011] S4. Add material A to solution a, mix, wash and dry to obtain a biochar adsorption material loaded with ferrite nanoparticles.

[0012] Biochar is a commercial product with good acid resistance and thermal stability. Biochar has a large specific surface area, a high cation exchange capacity, and is rich in oxygen-containing functional groups, so it has a good ability to exchange heavy metal ions. After the biochar is treated with nitric acid to remove surface impurities, the surface becomes rough. Then, after being placed in a mixed solution of iron salt and sodium salt and shaken, a hydroxyl iron loading layer is formed on the surface of the biochar material. The sodium ions in the solution do not react with arsenic ions, and the sodium ions will reduce the side reactions of iron ions, which can improve the utilization rate of iron ions, thereby obtaining a biochar adsorption material loaded with ferrite nanoparticles. When this biochar adsorption material loaded with ferrite nanoparticles is used to repair heavy metal pollution, the surface and internal pores of the material become rougher due to acid washing, which accelerates the adsorption of heavy metal arsenic ions by the material. In addition, the Fe-OH functional group reacts with As to further improve the adsorption effect.

[0013] Preferably, in S1, the particle size of the biochar after screening is 3mm-15mm. The biochar is screened through a 15mm mesh screen and a 3mm mesh screen in sequence. After the biochar is screened through a 15mm mesh screen, the biochar below the screen is screened through a 3mm mesh screen, and the biochar above the screen is retained, and the particle size range of the retained biochar is 3mm to 15mm. The screened biochar has a significant particle size compared to powdered biochar, is not easy to disperse into the repaired medium, and is easy to separate from the repaired medium; compared to large materials, biochar of this particle size can be filled with a wider range of applicability, increases the overall density during storage and transportation, reduces warehouse capacity, and saves transportation costs.

[0014] Preferably, ultrapure water or purified water is used in the cleaning process in the method for preparing the biochar adsorption material loaded with ferrite nanoparticles.

[0015] Preferably, in S2, the volume concentration of nitric acid is 1% to 10%, preferably 2% to 5%; the mass volume ratio of pretreated biochar and nitric acid solution is 1: (2 to 10) g / mL, preferably 1: (3 to 6) g / mL.

[0016] Preferably, in S2, the mixing time is 2 to 6 hours, the mixing temperature is 20 to 30° C., and the mixing rate is 100 to 200 rpm / min; the drying temperature is 60 to 90° C., and the drying time is 1 to 3 hours.

[0017] Preferably, in S3, the water-soluble iron salt is at least one of ferric nitrate and ferric sulfate, and the water-soluble sodium salt is at least one of sodium nitrate and sodium sulfate.

[0018] Preferably, in S3, the mass fraction of the iron salt solution is 0.5% to 2%, preferably 0.8% to 1.6%, and the mass fraction of the sodium salt solution is 1% to 3%, preferably 1.4% to 2.2%.

[0019] Preferably, in S3, the mass volume ratio of material A to solution a is 1:(5-15) g / mL, preferably 1:(8-12) g / mL.

[0020] Preferably, in S4, the mixing time is 2 to 9 hours, the mixing temperature is 20 to 30° C., and the mixing rate is 100 to 200 rpm / min; the drying temperature is 60 to 90° C., and the drying time is 1 to 3 hours.

[0021] A biochar adsorption material loaded with ferrite nanoparticles prepared by the above preparation method.

[0022] An application of a biochar adsorption material loaded with ferrite nanoparticles, the biochar adsorption material loaded with ferrite nanoparticles is applied to a permeable reaction wall medium, and the permeable reaction wall can be used to remove arsenic ions in soil or water contaminated by heavy metals. When the biochar adsorption material loaded with ferrite nanoparticles of the present invention is used in a permeable reaction wall medium, the adsorption capacity and service life of the reaction wall can be improved, and the production cost can be reduced.

[0023] The ferric nitrate in the solution of the present invention is a strong acid and weak base salt, which will be hydrolyzed to form nitric acid. Nitric acid acts as an oxidant and biochar acts as a reductant. Under heating conditions, the nitric acid combines with hydrogen ions to undergo a redox reaction. Due to the consumption of hydrogen ions, excess hydroxide ions combine with iron ions to form a precipitate of ferric hydroxide, which is deposited on the surface of biochar to obtain iron-modified biochar. During the modification process, the addition of sulfate ions can provide an appropriate ionic environment, obtain more hydroxide ions by combining more hydrogen ions, thereby creating a suitable pH value and promoting the formation of ferric hydroxide in the main reaction.

[0024] The main function of sodium sulfate in the solution is to increase the ionic strength. Sodium sulfate provides additional ions to increase the ionic strength of the solution, which helps to increase the collision frequency between reactants and promote the precipitation reaction. 2+ Ions and Mg 2+ Ions will react with As(Ⅲ) / As(Ⅴ) to form Ca(AsO2)2, CaAsO2OH·H2O and Ca5(AsO4)3OH, as well as Mg(HAsO4)2 and (Mg3(AsO4)2, etc., which will be deposited in the pore structure of biochar. Sodium ions will not react with arsenic ions, and sodium ions will reduce the side reactions of iron ions, thereby improving the utilization rate of iron ions.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The biochar adsorption material loaded with ferrite nanoparticles of the present invention controls the ratio of each component and the appropriate raw material ratio, thereby obtaining a biochar adsorption material loaded with ferrite nanoparticles for permeable reaction walls with strong adsorption and catalytic ability, which can efficiently adsorb arsenic ions in pollutants.

[0027] 2. In the soil remediation process of the present invention, the usage amount of the biochar adsorption material loaded with ferrite nanoparticles is extremely low, and the usage efficiency of the biochar adsorption material loaded with ferrite nanoparticles is high.

[0028] 3. The ferrite nanoparticle-loaded biochar adsorption material of the present invention uses raw materials from a wide range of sources, is low in price, and has a simple preparation process, and is suitable for large-scale production and processing.

[0029] 4. The biochar adsorption material loaded with ferrite nanoparticles of the present invention is a porous material with self-supporting properties and a certain particle size, which facilitates solid-liquid separation. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is the scanning electron microscope (SEM) image of the unmodified biochar in Example 1.

[0031] Figure 2 This is the SEM image of modified biochar in Example 1

[0032] Figure 3 Comparison of X-ray diffraction (XRD) analysis of biochar before and after modification in Example 1

[0033] Figure 4 The X-ray photoelectron spectrometer (XPS) analysis diagram of biochar before and after modification in Example 1

[0034] Figure 5 Comparison of the adsorption of heavy metal arsenic by unmodified and modified biochar in Example 1 DETAILED DESCRIPTION

[0035] The present invention will be described in detail below in conjunction with the embodiments. It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present invention can be combined with each other. Unless otherwise specified, the following percentages are all weight percentages.

[0036] Example 1

[0037] The present invention provides a biochar adsorption material loaded with ferrite nanoparticles, which is prepared by the following steps:

[0038] Step S1: Screen the biochar using 3 mm and 15 mm mesh screens to select biochar with a particle size of 3 mm to 15 mm, remove fine powder and large particles of biochar, then rinse with pure water, dry naturally or place in an oven to heat and dry to obtain pretreated biochar, and place in a drying device for later use;

[0039] Step S2: the pretreated biochar is mixed with a nitric acid solution having a volume concentration of 2% at a mass volume ratio of 1:3.3 g / mL, and then rinsed with pure water, filtered, and dried naturally or placed in an oven to obtain material A (C), which is placed in a drying device for later use;

[0040] Step S3: Use ferric nitrate nonahydrate reagent, sodium sulfate reagent and pure water in a mass volume ratio of 10.1:1000 g / mL and 14.2:1000 g / mL respectively to mix and stir to prepare an iron salt and sodium salt mixed solution, and then mix the material A with the iron salt and sodium salt mixed solution in a mass volume ratio of 1:10 g / mL and oscillate at 40°C for 8 hours. After completion, take out the material A, rinse it with pure water, and then put it into an oven for heating and drying at a drying temperature of 60 to 90°C to obtain a modified biochar adsorption material (Fe-C-1).

[0041] Example 2

[0042] The present invention provides a biochar adsorption material loaded with ferrite nanoparticles, which is prepared by the following steps:

[0043] Step S1: Screen the biochar using 3 mm and 15 mm mesh screens to select biochar with a particle size of 3 mm to 15 mm, remove fine powder and large particles of biochar, then rinse with pure water, dry naturally or place in an oven to heat and dry to obtain pretreated biochar, and place in a drying device for later use;

[0044] Step S2: the pretreated biochar is mixed with a nitric acid solution having a volume concentration of 2% at a mass volume ratio of 1:3.3 g / mL, and then rinsed with pure water, filtered, and dried naturally or placed in an oven to obtain material A (C), which is placed in a drying device for later use;

[0045] Step S3: Use ferric nitrate nonahydrate reagent, sodium sulfate reagent and pure water in a mass volume ratio of 12.62:1000 g / mL and 17.75:1000 g / mL respectively, mix and stir to prepare an iron salt and sodium salt mixed solution, then mix the material A with the iron salt and sodium salt mixed solution in a mass volume ratio of 1:10 g / mL, and oscillate at 40°C for 8h. After completion, take out the material A, rinse it with pure water, and then put it into an oven for heating and drying, the drying temperature is 60-90°C, to obtain a modified biochar adsorption material (Fe-C-2).

[0046] Example 3

[0047] The present invention provides a biochar adsorption material loaded with ferrite nanoparticles, which is prepared by the following steps:

[0048] Step S1: Screen the biochar using 3 mm and 15 mm mesh screens to select biochar with a particle size of 3 mm to 15 mm, remove fine powder and large particles of biochar, then rinse with pure water, dry naturally or place in an oven to heat and dry to obtain pretreated biochar, and place in a drying device for later use;

[0049] Step S2: the pretreated biochar is mixed with a nitric acid solution having a volume concentration of 2% at a mass volume ratio of 1:3.3 g / mL, rinsed with pure water, filtered, and dried naturally or placed in an oven to obtain material A (C), which is placed in a drying device for later use;

[0050] Step S3: Use ferric nitrate nonahydrate reagent, sodium sulfate reagent and pure water in a mass volume ratio of 15.15:1000 g / mL and 21.15:1000 g / mL respectively, mix and stir to prepare an iron salt and sodium salt mixed solution, then mix the material A with the iron salt and sodium salt mixed solution in a mass volume ratio of 1:10 g / mL, and oscillate at 40°C for 8h. After completion, take out the material A, rinse it with pure water, and then put it into an oven for heating and drying, the drying temperature is 60-90°C, to obtain a modified biochar adsorption material (Fe-C-3).

[0051] Biochar is a commercial product, and its surface structure is as follows: Figure 1 As shown in Figure 2, at a scale of 2 μm, there are a large number of granular structural impurities on the surface of the original biochar. After acid washing and modification, the impurities on the surface of the biochar are removed ( Figure 2 ). XRD analysis of biochar before and after modification showed that FeOOH crystals were formed on the surface of biochar after modification ( Figure 3 ), and XPS characterization proved that there were divalent Fe( Figure 4 ).

[0052] 200 mg of the iron-modified biochar adsorption material (Fe-C-1) prepared in Example 1 and the ordinary biochar material were added to 100 mL of 560 mg / L arsenic ion solution, shaken at 150 rpm and 25°C in a constant temperature shaker, and the sample was filtered through a 0.45 μm water phase filter, and the concentration of arsenic ions in the solution was measured using an inductively coupled plasma emission spectrometer. The experimental results are shown in Figure 2. Figure 5As shown, after three days of reaction, the original biochar adsorption material adsorbed 0.87 mg / g of As in water, and the iron salt-loaded biochar adsorbed 2.32 mg / g. The adsorption performance of the iron salt-loaded biochar was 2.67 times that of the original biochar.

[0053] The same mass of the biochar adsorption materials prepared in Example 2 and Example 3 were taken for the same experimental test. After three days of reaction, the adsorption values ​​reached were 1.59 (Fe-C-2) and 1.96 mg / g (Fe-C-3), respectively. The adsorption performance of the biochar adsorption material prepared in Example 1 was significantly better than that of the biochar adsorption materials prepared in Examples 2 and 3.

[0054] 800 mg of the modified biochar adsorption material prepared in Example 1 was added to 25 g of arsenic-contaminated wet soil actually collected. The amount of arsenic in the arsenic-contaminated wet soil was 288 mg / kg, of which only 19% was non-residual arsenic. The mixture was stirred evenly and aged for 3 days. The modified biochar material was removed from the soil, soil digestion was performed, and the total arsenic content of the solution soil was measured using an inductively coupled plasma emission spectrometer. The experimental results show that the modified biochar material was recovered after addition, effectively reducing the total arsenic in the soil to 200 mg / kg, of which the mass fraction of non-residual arsenic was reduced to 4%. The removal rate of total arsenic in the soil reached 30.4%, and the removal rate of non-residual arsenic reached 85.4%, so the content of non-residual arsenic in the soil can be effectively reduced.

[0055] The contents explained in the above embodiments should be understood as these embodiments are only used to more clearly illustrate the present invention, and are not used to limit the scope of the present invention. After reading the present invention, various equivalent forms of modifications to the present invention by those skilled in the art all fall within the scope defined by the claims attached to this application.

Claims

1. A method for preparing a biochar adsorption material loaded with ferrite nanoparticles, characterized in that: The following steps are involved: S1, screening, washing and drying the biochar to obtain pretreated biochar; S2, adding the pretreated biochar to the nitric acid solution, mixing, washing, filtering, and drying to obtain material A; S3, dissolving a water-soluble iron salt and a water-soluble sodium salt in water respectively to obtain an iron salt solution and a sodium salt solution, and mixing the iron salt solution and the sodium salt solution to obtain a solution a; S4. Add material A to solution a, mix, wash and dry to obtain a biochar adsorption material loaded with ferrite nanoparticles.

2. The method for preparing the biochar adsorption material loaded with ferrite nanoparticles according to claim 1, characterized in that: In S1, the particle size of biochar after sieving is 3 mm-15 mm.

3. The method for preparing the biochar adsorption material loaded with ferrite nanoparticles according to claim 1, characterized in that: In S2, the mixing time is 2 to 6 hours, the mixing temperature is 20 to 30° C., and the mixing rate is 100 to 200 rpm / min; the drying temperature is 60 to 90° C., and the drying time is 1 to 3 hours.

4. The method for preparing the biochar adsorption material loaded with ferrite nanoparticles according to claim 1, characterized in that: Ultrapure water or purified water is used during the cleaning process.

5. The method for preparing the biochar adsorption material loaded with ferrite nanoparticles according to claim 1, characterized in that: In S2, the mass volume ratio of the pretreated biochar and the nitric acid solution is 1: (2-10) g / mL, preferably 1: (3-6) g / mL; the volume concentration of nitric acid is 1% to 10%, preferably 2% to 5%.

6. The method for preparing the biochar adsorption material loaded with ferrite nanoparticles according to claim 1, characterized in that: In S4, the mixing time is 2 to 9 hours, the mixing temperature is 20 to 30° C., and the mixing rate is 100 to 200 rpm / min; the drying temperature is 60 to 90° C., and the drying time is 1 to 3 hours.

7. The method for preparing the biochar adsorption material loaded with ferrite nanoparticles according to claim 1, characterized in that: In S3, the water-soluble iron salt is at least one of iron nitrate and iron sulfate, and the water-soluble sodium salt is at least one of sodium nitrate and sodium sulfate.

8. The method for preparing the biochar adsorption material loaded with ferrite nanoparticles according to claim 1, characterized in that: In S3, the mass fraction of the iron salt solution is 0.5% to 2%, preferably 0.8% to 1.6%; the mass fraction of the sodium salt solution is 1% to 3%, preferably 1.4% to 2.2%.

9. The method for preparing the biochar adsorption material loaded with ferrite nanoparticles according to claim 1, characterized in that: In S4, the mass volume ratio of material A to solution a is 1:(5-15) g / mL, preferably 1:(8-12) g / mL.

10. A biochar adsorption material loaded with ferrite nanoparticles, prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Iron-based soil remediation agent and preparation method thereof

    CN110964536A

Cited By

  • Alkali metal-biochar composite material as well as preparation method and application thereof

    CN121466980A

  • An alkali metal-biochar composite material, its preparation method and application

    CN121466980B